PTU-135 Mechanism of Action for Linaclotide-Induced Abdominal Pain Relief. (4th June 2013) - Brierley, S M; Castro, J; Harrington, A; Hughes, P; Martin, C; Silos-Santiago, A; Kurtz, C; Blackshaw, A
Abstract : Introduction: Cyclic GMP (cGMP) is a 2nd messenger produced in intestinal epithelial cells in response to guanylate cyclase C receptor (GCC) activation. Linaclotide (LIN), an investigational GCC agonist (GCCA), improved constipation and reduced abdominal pain in patients with irritable bowel syndrome with constipation (IBS-C) in clinical trials. We have shown that exogenous extracellular cGMP has contrasting effects on colorectal (CR) afferent mechanosensitivity. 1 Here we assessed the effects of GCCAs on CR afferent mechanosensitivity in healthy and chronic visceral hypersensitivity (CVH) mouse models Methods: We investigated CVH in healthy mice and CVH 28 days post-TNBS administration, when inflammation had resolved and nociceptors were mechanically hypersensitive. Mechanosensory responses of CR splanchnic nociceptors and pelvic mucosal afferents were compared in vitro ± GCCAs STc (1, 50, 250, 1000nM) and LIN (1, 30, 100, 300, 1000nM), which were applied individually to the CR mucosal surface. GCC expression in the CR mucosa was determined via qRT-PCR Results: In healthy mice, STc dose-dependently (50, 250, 1000nM) reduced nociceptor mechanosensitivity (max. effect at 1000nM [n = 10], –38%; p < 0.001). This effect was more potent in CVH, with various doses of STc (1, 50, 250, 1000nM) all significantly reducing mechanosensitivity (max. effect at 1000 nM [n = 10], –53%; p < 0.001). In healthy mice, LIN significantly reduced nociceptor mechanosensitivity at doses of 300nM and 1000 nM (max. effect at 1000nM [n = 7], –48%; p < 0.01). In CVH this effect was dose-dependent and more potent, with LIN (100, 300, 1000 nM) significantly reducing nociceptor mechanosensitivity (max. effect at 1000 nM [n = 5], –59%; p < 0.001). By contrast, in pelvic nerves STc increased low-threshold pelvic mucosal afferent mechanosensitivity in healthy mice (n = 7; p < 0.001), an effect completely lost in CVH (n = 7; p > 0.05). qRT-PCR analysis revealed abundant GCC expression in CR mucosa of both healthy and CVH mice Conclusion: STc and LIN significantly reduced colonic nociceptor mechanosensitivity, with greatest effect in CVH. Although these overall effects mirror those of exogenously applied cGMP, GCCAs are more potent at inhibiting nociceptors. Overall, LIN induced the greatest inhibitory effects on nociceptors, particularly in CVH. Reducing colonic nociceptive input would help to reduce pain, which supports LIN clinical data showing a significant reduction in abdominal pain in humans with IBS-C. Increased mucosal afferent sensitivity may help coordinate defecation. Disclosure of Interest: S. Brierley Grant/Research Support from: Ironwood Pharmaceuticals, J. Castro: None Declared, A. Harrington: None Declared, P. Hughes: None Declared, C. Martin: None Declared, A. Silos-Santiago Employee of: Ironwood Pharmaceuticals, C. Kurtz Employee of: Ironwood Pharmaceuticals, A. Blackshaw Grant/Research Support from: Ironwood Pharmaceuticals. Reference: Gastro. 2011. Supported by Ironwood Pharmaceuticals Inc and by Forest Laboratories Inc. Medical writing assistance was provided by Complete Medical Communications, funded by Almirall.